2018
DOI: 10.1590/1413-81232018234.03662016
|View full text |Cite
|
Sign up to set email alerts
|

Excesso de peso e fatores associados em quilomboras do médio São Francisco baiano, Brasil

Abstract: The aim of this article was to analyze the prevalence of overweight and associated factors in adult quilombolas (inhabitants of black communities) from the Middle San Francisco, Bahia. Cross-sectional study with a sample of 112 adults. Overweight was evaluated by body mass index (BMI). Linear regression was used to test associations. The mean age of the participants was 42.1 (standard deviation 18.5) years and there was a predominance of females (55.4%). The prevalence of overweight was 27.7% (95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
15

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
1
0
15
Order By: Relevance
“…The divergence between the results suggests the need for monitoring these variables during life. In this research, BP disorders in adolescents are associated to obesity and indicates that the social gradient grows toward socially disadvantaged segments, a scenario observed in populations with low economic and schooling levels, corroborating with environmental inequities [42, 43] and health services [44], sine qua nom gears for health promotion and prevention of cardiovascular diseases (CVD).…”
Section: Discussionsupporting
confidence: 73%
“…The divergence between the results suggests the need for monitoring these variables during life. In this research, BP disorders in adolescents are associated to obesity and indicates that the social gradient grows toward socially disadvantaged segments, a scenario observed in populations with low economic and schooling levels, corroborating with environmental inequities [42, 43] and health services [44], sine qua nom gears for health promotion and prevention of cardiovascular diseases (CVD).…”
Section: Discussionsupporting
confidence: 73%
“…Estes dados corroboram com o estudo transversal realizado na Comunidade Quilombola de Tomé Nunes-Bahia, que ao analisar a prevalência do excesso de peso e os fatores associados em 112 adultos membros de uma comunidade quilombola identificaram 66,1% de eutrófico e 27,7% com excesso de peso. 9 Todavia, esses resultados diferem dos demais achados literários os quais obtiveram em seus estudos alto índice de sobrepeso/obesidade, autoconsumo de alimentos gordurosos e de sal. 3,12,14 Embora o cálculo do IMC seja a ferramenta mais utilizada em pesquisas para classificar a obesidade, não é capaz de distinguir massa magra de massa adiposa, diferenciar a distribuição de gordura corporal ou detectar o aumento de gordura, podendo ser menos preciso em indivíduos mais idosos, em decorrência da perda de massa magra e diminuição do peso, e superestimado em indivíduos musculosos.…”
Section: Discussão Discussão Discussão Discussãounclassified
“…Despite the limited number of studies, a high prevalence of MetS among quilombolas has been reported [33][34][35][36] . Furthermore, anthropometric studies have shown high rates of overweight and obesity in this population 37,38 . However, we found no studies involving the quilombo population that investigated the accuracy of OIs and established cutoff points for the identification of individuals at increased risk and their immediate referral to specialized health services for diagnostic confirmation and treatment of MetS.…”
Section: Introductionmentioning
confidence: 95%